2006
DOI: 10.1002/ajmg.a.31296
|View full text |Cite
|
Sign up to set email alerts
|

Holoprosencephaly: Clinical evaluation on audiological and brainstem electrophysiological profiles

Abstract: This study evaluated audiological and electrophysiological profiles in 13 patients with holoprosencephaly. All patients had imaging evaluation by magnetic resonance imaging and molecular screening for the genes SHH, GLI2, and SIX3. Each patient underwent clinical (otological and vestibular antecedents, otoscopy) and instrumental (tympanometry, auditory brainstem response-ABR) evaluation to compare hearing and the electrophysiological profile possibly occurring in patients with these mutations. To our knowledge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
0
5
0
1
Order By: Relevance
“…Most children with HPE have severe motor impairment and little expressive language ability [16][17][18][19]. Antoneli et al showed that patients with alobar HPE had abnormalities in ABRs represented by increased interwave latencies in addition to those with absent waves, whereas patients with lobar HPE had normal ABRs [20]. In our study, four of the nine patients with lobar HPE and the one patient with semilobar HPE had abnormal results for ABRs.…”
Section: Discussionmentioning
confidence: 64%
“…Most children with HPE have severe motor impairment and little expressive language ability [16][17][18][19]. Antoneli et al showed that patients with alobar HPE had abnormalities in ABRs represented by increased interwave latencies in addition to those with absent waves, whereas patients with lobar HPE had normal ABRs [20]. In our study, four of the nine patients with lobar HPE and the one patient with semilobar HPE had abnormal results for ABRs.…”
Section: Discussionmentioning
confidence: 64%
“…This study was approved by the Ethics Committee of the Hospital de Reabilitacão de Anomalias Craniofaciais (HRAC‐USP) after obtaining informed consent from participants. The sample consisted of patients of our center with classical HPE phenotype and with the HPE‐like phenotype previously reported in the American Journal of Medical Genetics 2006–2009 [Ribeiro and Richieri‐Costa, 2005a,b; Antoneli et al, 2006; Rahimov et al, 2006; Ribeiro et al, 2006a,b; Richieri‐Costa and Ribeiro, 2006a,b; Zechi‐Ceide et al, 2009] and shown in Figures 1–6. To these cases, we added 35 new patients with HPE, 36 patients with HPE‐L phenotype, and 6 patients with HPE‐L associated with SCMI.…”
Section: Methodsmentioning
confidence: 99%
“…Neural integrity was evaluated with stimulus clicks (0.1 millisecond in duration, 21.1 clicks per second) at 80 dBHL. Absolute peak latency and interpeak latencies of each patient were compared with normal parameters previously reported (Antoneli et al, 2006) and interpreted according to the presence or absence of impairment of the central auditory pathways, independent of the audiological status for hearing loss.…”
Section: Methodsmentioning
confidence: 99%